Women Count A Guide to Changing the World - Bulkeley Butler, Susan (Purdue University Press, 2011)
Throughout history, women have struggled to change the workplace, change government, change society. So what's next? It's time for women to change the world! Whether on the job, in politics, or in their community, there has never been a better time for women to make a difference in the world, contends author, mentor, and corporate pioneer Susan Bulkeley Butler in Women Count: A Guide to Changing the World. Through her experience as the first female partner of a major consulting firm and founder of the Susan Bulkeley Butler Institute for the Development of Women Leaders, Butler's unique insights have changed the lives of countless women. In Women Count, she shows readers how to change the world through a series of inspiring case studies that chronicle how she and other pioneering women in a range of fields have done so in years past. Women represent half of the country's population, half of the country's college graduates, and around 50 percent of the country's workforce. Butler envisions a day when they will also make up their fair share of elected and appointed positions, including in corporate boardrooms. Amid financial meltdowns, wars, and societal struggles, never before has the world so greatly needed the unique abilities of women to lead the way. But as history has shown, to make change, women must step into their power and become "women who count," Butler contends. Then and only then, she argues, can women truly change the world.